x÷(x分之1-y分之1)
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/06 23:36:00
x÷(x分之1-y分之1)x÷(x分之1-y分之1)x÷(x分之1-y分之1)=x除以(xy分之y-x)=x•(y-x分之xy)=y-x分之x^2y
x÷(x分之1-y分之1)
x÷(x分之1-y分之1)
x÷(x分之1-y分之1)
=x除以(xy分之y-x)
=x•(y-x分之xy)
=y-x分之x^2y
化简1-x分之y分之1+x分之y
x÷(x分之1-y分之1)
2x分之1- x+y分之1(2x分之x+y -x-y)化简
1- X+Y分之X-Y 分之 1+ X+Y分之X-Y
1- X+Y分之X-Y 分之 1+ X+Y分之X-Y
若X分之1+Y分之1=X+Y分之1 求X分之Y+Y分之X
x分之1+y分之1那个
数学题(1-y+x分之y)÷y的平方-x的平方分之x
x²-y²分之xy÷(xy分之1-x+y分之1)
计算(3y分之2x)×(4y分之3x)÷(4分之1xy)
x等于5分之1y等于7分之1求代数式x分之1加y分之1÷x分之1减y分之1
x-y分之1除以y-x分之1
化简(x+y分之1)(y+x分之1)
(x-y分之1)除以(y-x分之1)
(1+x分之y)除以(1-x分之y)
y-x分之1+2y-2x分之1
1-x分之2y-x-1分之y
1.计算①(x-1-x+1分之8)×x+3分之x+1;②x+3y分之x-y÷x²+6xy+9y²分之x²-y²-x+y分之2y;③(x-x+1分之2x)÷x²-1分之x²-2x+1④(x²-2x分之x+2-x²-4x+4分之x-1)÷x³-2x²分之x-4